Kepemimpinan Transformasional dan Motivasi pada Kinerja Masyarakat: Studi Kasus Organisasi Badan Usaha Milik Desa (BUMDes) di Kabupaten Semarang Jawa Tengah - Rachmawati, Meida; Dewantoro, Bambang; Dasmadi; Novandalina, Arini; Budiyono, Rokhmad (Research and Development Agency Ministry of Home Affairs, 2021)
Transformational Leadership in an organization has a significant influence on the success and dynamics of an organization. Village-Owned Enterprise (BUMDes) as an organization is expected to increase the Village's original income and prosper the village community, based on the mandate of Law no. 6 of 2014. In the increasingly rapid corporate competition, several problems are often faced by business actors. In terms of capital in developing a business, based on this phenomenon, BUMDes are presented and built in the form of an organization with a spirit of togetherness in exploring and recognizing Village Potential. Therefore, one way to succeed in development in village income is to increase village income. The amount of village income is influenced by the performance of BUMDes in managing and maximizing existing assets in the Village. The purpose of writing this literature study is to identify Transformational Leadership in improving the performance of Village Owned Enterprises (BUMDes). The method used a literature study. The results obtained are to measure the influence of Transformational Leadership and Motivation on Community Performance. This study concludes that Leadership in the management of BUMDes in Semarang Regency can reflect Transformational Leadership.